2020
DOI: 10.1148/ryct.2020200110
|View full text |Cite|
|
Sign up to set email alerts
|

Chest CT Findings in Cases from the Cruise Ship Diamond Princess with Coronavirus Disease (COVID-19)

Abstract: ・Of 104 cases analyzed, 76 (73%) were asymptomatic, 41 (54%) of which had pneumonic changes on CT. Other 28 (27%) cases were symptomatic, 22 (79%) of which had abnormal CT findings. ・Asymptomatic cases showed more GGO predominance over consolidation (83%), while symptomatic cases were more likely to show a consolidation predominance over GGO (41%). ・Asymptomatic cases showed milder CT severity score than symptomatic cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
280
2
17

Year Published

2020
2020
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 378 publications
(312 citation statements)
references
References 21 publications
13
280
2
17
Order By: Relevance
“…Given the proportion of patients who developed symptoms prior to initiating treatment, our experience supports the recommendation for rigorous screening in advance of treatment initiation as well as between appointments (e.g., when simulation and treatment start are >1 week apart). In addition, with increasing reports of asymptomatic transmission, routine inspection of lung imaging on simulation and cone-beam CT images is strongly encouraged [6][7]. Patients on-treatment were less commonly affected, which may be due to greater precautions to self-quarantine.…”
Section: Discussionmentioning
confidence: 99%
“…Given the proportion of patients who developed symptoms prior to initiating treatment, our experience supports the recommendation for rigorous screening in advance of treatment initiation as well as between appointments (e.g., when simulation and treatment start are >1 week apart). In addition, with increasing reports of asymptomatic transmission, routine inspection of lung imaging on simulation and cone-beam CT images is strongly encouraged [6][7]. Patients on-treatment were less commonly affected, which may be due to greater precautions to self-quarantine.…”
Section: Discussionmentioning
confidence: 99%
“…Further, patients testing positive for COVID-19 can be asymptomatic despite significant abnormalities noted on chest computed tomography (CT) scan and there appears to be significant risk of asymptomatic transmission of the disease. [9][10] Therefore, a balance must be struck in identifying appropriate patients for invasive approaches to AMI regardless of their COVID-19 status, and maintaining the safety of healthcare workers who might be exposed to the disease as well as minimizing contamination of cardiac catheterization laboratory (CCL) facilities. The need for additional patient evaluation might translate into some delays in reperfusion.…”
Section: Methodsmentioning
confidence: 99%
“…After day 14, improvement in imaging findings was reported in 75% of the patients, including decreased number of involved lobes and resolution of crazy paving pattern and consolidative opacities. [37] A recent study showed that 54% of the asymptomatic patients had pneumonic changes on chest CT, [38] but it should be kept in mind that 56% of the patients in the early period of the disease may have a normal CT. [39] If the patient develops symptoms and the symptoms cannot be explained due to the clinical status of the patient, a new evaluation should be required (Figs. 1ab, 2).…”
Section: A Chest Ct Scan Should Be Added Into Routine Diagnostic Toolmentioning
confidence: 99%